Learning Organization Pada Madrasah Aliyah Negeri 1 Kota Bandar Lampung - Suzana, Hera; Pahrudin, Agus; Patimah, Siti; Junaidah, Junaidah; Ayu, Sovia Mas (El-Idare, 2023)
A high level of public trust in the transformations carried out by the institution, apart from that the achievements produced by the students are quite encouraging as well as the good teaching capabilities and excellent programs. This study used a descriptive qualitative approach with data collection using interviews, observation, and documentation. In data analysis with the stages of data reduction, data display, and drawing conclusions. The results of this study indicate that: 1) System thinking at MAN 1 Bandar Lampung in the formulation of the vision is carried out jointly by involving all stakeholders to see opportunities and challenges. 2) Personal mastery can be seen from the visionary madrasa head as a professional trainer so that he is able to develop the professionalism of the people he leads through various education and training programs. 3) Mental models are built through good human relations so as to improve employee performance. 4) Shared Vision by always communicating or disseminating the vision, by communicating the values ​​contained in the vision. 5) Team Learning by always synergizing all teachers and students about what is the vision of the madrasa and trying to realize the vision.